2013
DOI: 10.1002/jhet.1573
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some New 1,2,3,4-Tetrahydropyrimidine-2-thione and Their Thiazolo[3,2-a]pyrimidine, Thiazino and Benzothiazepine Derivatives

Abstract: The starting N‐(2‐pyridyl)‐6‐methyl‐4‐phenyl‐2‐thioxo‐1,2,3,4‐tetrahydropyrimidine‐5‐carboxamide (4) was used as a key intermediate for the synthesis of new 1,2,3,4‐tetrahydropyrimidine‐2‐thione and their thiazolo[3,2‐a]pyrimidine, thiazino and benzothiazipen derivatives. The reaction of 4 with haloketones in ethanol catalyzed by base afforded the corresponding thiophenopyrimidine and pyrimidothiazipine derivatives 5, 6, 7, 8, 9, 10. Methylation and formylation of 4 led to the pyrimidine derivatives 15 and 16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the literature (Danelet al 1998;Fadda et al 2013;Abdel Moty et al 2016) there is evidence that the reaction formed product 3 may be subject to intramolecular cyclization with the nitrogen N 1 and N 3 atoms, and it is difficult to stop the reaction at the stage of the formation of S-derivatives. This is precisely what happened in our attempt to get compound 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature (Danelet al 1998;Fadda et al 2013;Abdel Moty et al 2016) there is evidence that the reaction formed product 3 may be subject to intramolecular cyclization with the nitrogen N 1 and N 3 atoms, and it is difficult to stop the reaction at the stage of the formation of S-derivatives. This is precisely what happened in our attempt to get compound 3.…”
Section: Resultsmentioning
confidence: 99%
“…Danel et al (1998) found that the N 3 atom is more reactive than N 1 due to the influence of the neighbouring carbonyl group, therefore we assumed that the reaction products are compounds of type 3 and 5. In addition, a group of authors (Fadda et al 2013) argues that boiling under the above conditions, 6-methyl-thiouracy 1 with phenacyl bromide 2 precisely results in the formation of 7-methyl-3-phenyl-5H-thiazolo[3,2-a] pyrimidine 5.1. However, by analyzing the 1 H NMR spectra, the expected singlet signal of the proton at position 2 of the thiazole ring of compound 5.1 in the region characteristic of aromatic protons was not found.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, these compounds have been used as precursors for the synthesis of some condensed derivatives. For example, the conversion of 3,4‐dihydropyrimidin‐2(1 H )‐thione derivatives 77 into the corresponding 3‐oxo‐3,5‐dihydro‐2 H ‐thiazolo[3,2‐ a ]pyrimidines 78 has been widely described (Scheme ).…”
Section: Intramolecular Cycloadditions Of Partially Saturated Pyrimidmentioning
confidence: 99%
“…As condensing agents for this cyclization were used halogen‐derived doubly electrophilic building blocks such as chloroacetyl chloride , methyl chloroacetate , ethyl chloroacetate , ethyl bromoacetate , chloroacetic acid , bromoacetic acid , and 2‐haloacetamides (Scheme ). Carrying out this reaction in the presence of aromatic aldehydes afforded 2‐arylidene‐2,3‐dihydro‐ 5H ‐thiazolo[3,2‐ a ]pyrimidines 79 .…”
Section: Intramolecular Cycloadditions Of Partially Saturated Pyrimidmentioning
confidence: 99%
See 1 more Smart Citation